Community participation in mangrove forest conservation in Mendana Strait, Kong Kong, Johor - Zaleha, Kassim (Universiti Malaysia Terengganu, 2022)
Mangrove forest of Kong Kong in Johor, despite gazetted for wildlife refuge, is threatened due to the escalating exploitation for tourism, aquaculture, ship docking and transportation purposes. Adding to past concerns on the already widely contaminated Johor waters, the declining health of Kong Kong mangrove forest raised the urgency to gather data beyond the naked eye; the underlying reasons that encourage human activities in the proclaimed forest reserve. The fundamental elements that influence the local community’s participation in mangrove forest conservation ought to be highlighted as a determining factor in the effectiveness of this nature preservation effort. An initiative to empower Kong Kong local community participation in mangrove forest conservation was performed between 2017 to 2018. Through Knowledge Transfer Program, a survey was conducted among representatives of the local community of Kong Kong. The representatives (N = 79) of Selat Mendana community’s willingness to participate in mangrove conservation effort were examined based on their socioeconomic dependence towards Kong Kong mangrove forest resources and their perceived values of the forest to themselves. 56.9% (n = 45) from the overall respondents depended on mangrove forest resources as a source of income for commercial and tourism purposes, while 60.8% (n = 48) of the respondents possess commercial property to meet the aforementioned demands, in which these factors significantly influenced their socioeconomic dependence on the forest resources (p < .05) but not on their perceived participation in mangrove forest conservation (p > .05). The respondents’ mangrove resource dependence and perceived participation in mangrove forest conservation were negligibly correlated (p = .09, r = .19). To conclude, a local community of an area play vital role in the effectiveness of a nature preservation effort as they share space with the surrounding ecosystem.